2007
DOI: 10.1063/1.2715119
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of molecular beam epitaxy growth of GaN nanowires on Si(111)

Abstract: GaN nanowires have been grown without external catalyst on Si(111) substrates by plasma-assisted molecular beam epitaxy. Nanowire aspect ratios (length/diameter) of about 250 have been achieved. During the initial stage of the growth, there is a nucleation process in which the number of wires increases and the most probable nucleation diameter of about 10nm has been observed, which slowly increases with deposition time. For deposition time longer than the nucleation stage, the nanowire length as a function of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
234
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 221 publications
(248 citation statements)
references
References 21 publications
12
234
2
Order By: Relevance
“…Moreover, the proposed GaN nanorod growth mechanism assumes that the Ga diffusion process along the nanorod sidewalls up to its apex can be a major contribution, thus, the wider the nanorod, the smaller its growth rate. 38 The authors suggested that the nanorod starts to grow on a GaN island once it reaches its critical size and becomes stable, following a process that depends on two contributions, 27 namely, (i) Ga atoms impinging on the nanorod apex will incorporate directly to the crystal; and (ii) Ga atoms arriving to the substrate surface will diffuse to the nanorods base, climb along the lateral sidewalls up to their apex and incorporate to the crystal, 27,32,38 as shown by the diagram in Fig. 10(b).…”
Section: B Catalyst-free Gan Nanorod Growthmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the proposed GaN nanorod growth mechanism assumes that the Ga diffusion process along the nanorod sidewalls up to its apex can be a major contribution, thus, the wider the nanorod, the smaller its growth rate. 38 The authors suggested that the nanorod starts to grow on a GaN island once it reaches its critical size and becomes stable, following a process that depends on two contributions, 27 namely, (i) Ga atoms impinging on the nanorod apex will incorporate directly to the crystal; and (ii) Ga atoms arriving to the substrate surface will diffuse to the nanorods base, climb along the lateral sidewalls up to their apex and incorporate to the crystal, 27,32,38 as shown by the diagram in Fig. 10(b).…”
Section: B Catalyst-free Gan Nanorod Growthmentioning
confidence: 99%
“…Furthermore, a diffusion-induced growth model was suggested by Debnath et al, 38 as plotted in Fig. 11.…”
Section: B Catalyst-free Gan Nanorod Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9] The small footprint of the NWs on the substrate greatly relaxes issues related to the structural mismatch between substrate and NW. Many publications have already reported on the growth of homoepitaxial III-nitride NWs by plasma assisted molecular beam epitaxy ͑PAMBE͒, [10][11][12][13][14][15][16][17][18][19][20] including InGaN NWs on Si substrates. 21,22 However, to exploit the whole range of optoelectronic devices compatible with a NW design, the possibility to realize axial as well as radial hetero-and quantum structures is essential.…”
Section: Structural and Optical Properties Of Ingan-gan Nanowire Hetementioning
confidence: 99%
“…10-12͒ and NW ensembles 13,14 has been proven. However, the processes of nucleation [15][16][17][18][19] and diffusion of adatoms [20][21][22][23] on the NW still represent interesting and lively discussion subjects as not all the aspects have been clarified. In addition, the understanding of the growth leads to further improvements of sample quality and of the control over the structures, which in turn is beneficial for device performances.…”
mentioning
confidence: 99%